Plan de negocios para la creación de una empresa dedicada a la producción y comercialización en la ciudad de Quito de polvo de remolacha beterraga como edulcorante - Chauvin Solano, Mónica Guadalupe (2017)
The business plan of this document has as main objective to execute the corresponding actions to determine the feasibility of commercializing a sweetener based on beets in the supermarkets of the city of Quito. To this end, the analysis of environments is performed, where it can be verified that the social environment is favorable to the project, due to the existence of overweight and obesity among the population of the country. As far as customer research is concerned, the survey conducted allows the target market to be established between people between the ages of 25 and 54, especially women looking for alternative products to sweeten their food without the burden of carbohydrates and sugars in their regular diet. The marketing plan has a clear explanation related to the promotion of the product in the places of commercialization, through actions of direct communication and advertising in digital media. The financial plan estimated the initial investment of the project in the amount of $ 202,867, which is financed by equity capital of $ 121,720 and a bank loan of $ 81,147, projections of the cash of investor flow and Discount determine a net present value $ 53,767 and an internal rate of return of 30.72%. These indicators allow to recommend the execution of the business plan based on its organizational structure.